Evaluating hydropower and irrigation development in Sudan under climate change uncertainties - Basheer, Mohammed; Elnour, Zuhal; Pérez, Cristo Facundo; Liao, Wenxi; Siddig, Khalid; Ringler, Claudia (International Food Policy Research Institute, 2024)
Hydropower and irrigation development on the Nile in Sudan can help meet growing food and energy needs. However, these potential infrastructures must be evaluated considering climate change uncertainties and multisector socioeconomic trade-offs. Increased streamflow combined with the recently constructed Grand Ethiopian Renaissance Dam would provide reliable irrigation water supplies in Sudan under most climate change scenarios but there are distributional impacts.